2014
DOI: 10.1002/joc.4159
|View full text |Cite
|
Sign up to set email alerts
|

Trends in pre‐summer frontal and diurnal rainfall activities during 1982–2012 over Taiwan and Southeast China: characteristics and possible causes

Abstract: Frontal convection (FC) and diurnal convection (DC) are the two most frequently observed weather systems affecting the pre-summer (May and June, MJ) rainfall formation over Taiwan and Southeast China. Focusing on the time period of 1982-2012 MJ months, this study found that the occurrence frequency of FC has declined, but the occurrence frequency of DC has significantly increased over Taiwan and Southeast China. Diagnoses of the atmospheric thermodynamic conditions over the East Asian-Western North Pacific (EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 50 publications
7
40
0
Order By: Relevance
“…The thick line in Figure a represents the low‐pass‐filtered frequency through 11 year running average. The linear trend of the frequency during 1961–2012 (the time period focused in this study; blue line) and during 1982–2012 (the time period examined by Huang and Chen []; red line) are added in Figure a for discussions. (b) The temporal variation of CAR frequency (thin line), its related 10–20 year band‐pass‐filtered values (green line) and 4–8 year band‐pass‐filtered values (yellow line).…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…The thick line in Figure a represents the low‐pass‐filtered frequency through 11 year running average. The linear trend of the frequency during 1961–2012 (the time period focused in this study; blue line) and during 1982–2012 (the time period examined by Huang and Chen []; red line) are added in Figure a for discussions. (b) The temporal variation of CAR frequency (thin line), its related 10–20 year band‐pass‐filtered values (green line) and 4–8 year band‐pass‐filtered values (yellow line).…”
Section: Methodssupporting
confidence: 81%
“…By examining the trend in summer CAR in the Taipei basin (located in northern Taiwan), Chen et al [] noted an intensification of the summer CAR over the past 50 years and attributed this change to the strengthening urban heat island effect. Recently, Huang and Chen [] examining the trend in CAR activity over Taiwan during 1982–2012 Mei‐Yu season have suggested that the CAR has become more frequent and more intense since 1982. Because the formation of CAR in Taiwan is geographically dependent [ Huang and Wang , ], differences are likely to exist between the low‐frequency variations of CAR activity over different subregions in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 we show that Fig. 1 The first mode of EOF analysis on the long-term, 3-hourly TRMM 3B42 precipitation, following Huang and Chen (2015): a eigen-vector (E1) and b eigen-coefficient (PC1). In a, the domains of the Yangtze River regime (red dotted box) and southeast China regime (orange outline) are marked to help the discussions in the manuscript.…”
Section: Introductionmentioning
confidence: 89%
“…The spatial-temporal variations of diurnal rainfall were depicted by the Empirical Orthogonal Function (EOF) analysis applied on the long-term, 3-hourly TRMM precipitation, following Huang and Chen (2015). The first EOF (Fig.…”
Section: The Simulation Of Diurnal Variation At Present Climatementioning
confidence: 99%